Continued use of dorzolamide for the treatment of cystoid macular oedema in patients with retinitis pigmentosa. Issue 6 (10th January 2007) - Fishman, Gerald A; Apushkin, Marsha A
Abstract : Aim: To determine the value of a topical carbonic anhydrase inhibitor for extended treatment of cystoid macular oedema (CME) in patients with retinitis pigmentosa (RP). Method: Eight patients with RP and foveal cystic-appearing lesions observed on fundus examination and by optical coherence tomography (OCT) testing were treated with a topical form of carbonic anhydrase inhibitor. Results: Foveal cystic-like spaces were documented by OCT testing in all eight patients before treatment. All patients had a significant reduction in their foveal thickness (FT) and foveal zone thickness (FZT) in at least one eye after using 2% dorzolamide three times a day for 1 or 2 months. Six patients had an improvement in both eyes. After an additional 6–13 months of the same treatment regimen, out of six patients who had a sustained reduction in FT and FZT in at least one eye, four had this reduction in both eyes. While they were still taking Trusopt, a recurrence (rebound) of CME in both eyes was observed in two patients, whereas one patient had a sustained improvement in one eye and rebound of CME in the other eye. Out of 8 patients, 3 showed an improvement in their visual acuity by ⩾7 letters, in at least one eye, on Snellen acuity charts, which was determined as clinically significant. Conclusion: Results from this study suggest that patients with RP could potentially sustain a beneficial effect from continued treatment with a topical form of carbonic anhydrase inhibitor.